Performance Calculation of Floating Wind Turbine Tension Leg Platform in the South China Sea - Wang, Hai Feng; Fan, You Hua (Journal of Engineering and Technological Sciences, 2015)
The harvesting of wind energy is expected to increase greatly in thefuture because of its stability, abundance, and renewability in large coastal states such as China. The floating support structure will likely become the major structural form for wind turbines in the future due to its cost advantages when the water depth reaches 50 m. The 5MW wind turbine model from National Renewable Energy Lab (NREL) and the modified tension leg platform model proposed by Harbin Institute of Technology (HIT) were applied to certain sea conditions in the South China Sea in order to consider the effects of external load coupling actions. In this study, the internal force, mooring system force, as well as the acceleration, displacement and velocity of the floating structure of the modified HIT Tension Leg Platform (HIT-TLP) were calculated. During this process, the physical parameters of its tension leg structure at a specific frequency domain were obtained to find the technical reserves for its practical application in the future.